Design and Deformation Analysis of MEMS Piezoresistive Pressure Sensors Using COMSOL for Sensitivity Enhancement via Material Optimization (Bangladesh Journal of Physics, 2026)
Piezoresistive pressure sensors are critical in aerospace, biomedical and industrial applications where high sensitivity and reliability are essential. This study presents a simulation-based performance analysis of MEMS piezoresistive pressure sensors using COMSOL Multiphysics 6.1. Four materials—Aluminum Gallium Arsenide (AlGaAs), Germanium (Ge), Silicon (Si) and Titanium Germanium Carbide (Ti₃GeC₂)—were evaluated under identical sensor architectures. The design features a square diaphragm with an X-shaped piezoresistor layout to intensify stress concentration and boost sensitivity. Simulations were conducted under pressure load of 100 kPa. Key performance indicators—diaphragm displacement, shear and von Mises stress and sensitivity (V/Pa)—were analyzed. Ti₃GeC₂ exhibited the highest sensitivity (5.08×10⁻⁶ V/Pa), outperforming Si by 49% and showed superior mechanical resilience with the lowest deflection. These results highlight Ti₃GeC₂ as a promising candidate for next-generation MEMS sensors operating in harsh environments. The model is built on fabrication-relevant parameters and provides predictive insight into material selection for high-performance piezoresistive sensors.Bangladesh Journal of Physics, Vol. 32, Issue 2, pp. 29 – 41, December 2025